Survival Strategies in Extreme Cold and Desiccation Adaptation Mechanisms and Their Applications (Advances in Experimental Medicine and Biology, 2018)
This book comprehensively describes biological phenomena, adaptation mechanisms, and strategies of living organisms to survive under extremely cold or desiccated conditions at molecular, cellular, and organ levels. It also provides tremendous potential for applications of the findings to a wide variety of industries. The volume consists of three parts: Part 1, Adaptation Mechanisms of Cold, and Part 2, Adaptation Mechanisms of Desiccation, collect up-to-date research on mechanisms and strategies of living organisms such as sleeping chironomids, polar marine fishes, hibernating mammals, bryophytes, dormant seeds, and boreal plants to survive under extreme cold and desiccated conditions at molecular, cellular, and organ levels. Part 3, Application Technologies from Laboratory to Society, covers various applications to a wide variety of industries such as the medical, food, and agricultural and life science industries. For example, biological knowledge of how plants and animals survive under cold, drought, and desiccated conditions may provide a hint on how we can improve crop production in a very fragile environment in global climate change. Unique molecules that protect cells during desiccation and freezing such as trehalose and antifreeze protein (AFP) have potential for use to preserve cells, tissues, and organs for the long term under very stable conditions. In addition, the current progress of supercooling technology of cells may lead us to solve problems of cellular high sensitivity to freezing injury, which will dramatically improve the usability of these cells. Furthermore, knowledge of water substitution and glass formation as major mechanisms for formulation designs and new drying technologies will contribute to the development of food preservation and drug delivery systems under dry conditions. Written by contributors who have been conducting cutting-edge science in related fields, this title is recommended to a wide variety of readers who are interested in learning from such organisms their strategies, mechanisms, and applications, and it will inspire researchers in various disciplines.